TYPES OF BOWS AND ARROWS IN TURKIC MILITARY ART (American Journal of Research in Humanities and Social Sciences, 2026)
The military success of the ancient Turkic states was closely connected with the development of advanced archery traditions. Among the various military technologies employed by Turkic warriors, composite bows and specialized arrows occupied a central position. This article examines the main types of bows and arrows used in Turkic military art, their construction, tactical functions, and contribution to military effectiveness. Using historical-comparative and source analysis methods, the study demonstrates that the diversity of bow and arrow types significantly enhanced the combat capabilities of Turkic armies and contributed to their dominance across the Eurasian steppes. The findings reveal that Turkic archery traditions influenced the military systems of later nomadic empires, including the Mongols and the Timurids.